Sensory and bromatological characterization of artisanal fresh panela cheese made from goat’s milk with a specific α-S1-casein genotype and cow’s milk - Arellano Vera, Williams; Martínez Morales, Sagnitet; Gill Langarica , Homar Rene; Sifuentes Rincón, Ana María (Indian Journal of Dairy Science, 2025)
The influence of AA and FF genotypes of α-S1-casein in goat milk was evaluated in relation to the bromatological and sensory characteristics of traditionally produced regional panela cheese made from a blend of goat and cow milk. A total of 68 Saanen and Creole goats were genotyped using the PCR-RFLP. Cheese was made with milk from goats with AA and FF genotypes and in 1:1 mixtures of goat milk (GM) and cow milk (CM), the mixed-milk cheeses were as follows: GMAA+CM, GMFF+CM, GMAF+CM, and a control made from non-genotyped goat milk and cow milk (GM+CM). Cheese yield, protein, fat, and moisture contents were determined. Sensory analysis was conducted on 15 attributes using a descriptive test with an unstructured linear scale. In the Saanen breed, six goats carried the A allele and four carried the F allele. In contrast, among the Creole goats, only the F allele was detected in the three individuals analyzed, with no occurrence of the A allele. GMAA+CM exhibited the highest protein content (22.91%) and the lowest goat flavor score (3.42), while GMFF+CM presented higher fat (21.06%) and moisture content (53.81%) along with a more intense goat flavor (4.67) (p < 0.05). No significant differences were found in cheese yield or goat odor intensity (p > 0.05). CSN1S1 genotyping enabled the production of goat and cow milk cheeses with a milder goat flavor, facilitating the development of products with enhanced bromatological properties and distinctive sensory profiles.